SOSIALISASI PEMASARAN PRODUK TANAMAN HERBAL UNTUK DAYA TAHAN TUBUH DI MASA COVID-19 PADA MASYARAKAT GAMPONG UJONG BAROH - Cut Devi Maulidasari; Damrus Damrus; Rusma Setiyana; Chairiyaton Chairiyaton; Cut Mega Putri (Jurnal Pengabdian Agro and Marine Industry, 2021)
AbstractAt the beginning of 2020 until now, the world, including Indonesia, was hit by a pandemic known as Coronavirus Disease 2019 (COVID-19). Currently, various efforts are continuously being made to fight against the pandemic, including creating the right vaccine so that this pandemic will end soon. In addition, in suppressing the pace of the pandemic so that it does not spread further and result in an increasing number of fatalities, it is necessary to comply with health protocols such as implementing 3M in daily life. The next thing that is no less important is adopting a healthy lifestyle so that the immune system in the body becomes good to deal with the high level of this pandemic. Furthermore, the use of herbal plants is also important as an alternative in increasing the immune system of the human body, for example, ginger and turmeric are believed to be one of the compositions for treating hepatitis. This condition is of course an opportunity for herbal plant cultivators to market the herbal plants they produce. Of course this requires marketing strategies such as the use of online media, promotions, and so on.Keyword: Covid-19, Herbal Plants, Marketing Strategy